2016
DOI: 10.1097/md.0000000000003741
|View full text |Cite
|
Sign up to set email alerts
|

Death Due to Intra-aortic Migration of Kirschner Wire From the Clavicle

Abstract: Migration of orthopedic fixation wires into the ascending aorta though a rare occurrence can have devastating consequences. Therefore, prompt recognition, with immediate and cautious retrieval of the implant is paramount in averting these complications.We present a case of a 5-year-old boy with the intra-aortic migration of a K-wire used for the treatment of a right clavicle fracture. He was transferred to us with a history of syncope, chest pain, and shortness of breath 7 days after K-wire placement, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
(71 reference statements)
0
22
0
5
Order By: Relevance
“…Drawn wires from titanium (Ti) and its alloys, stainless steels (SSs), and nitinol have been used in different medical devices such as cardiovascular stents [4], coronary guide catheter [5], coil occlusion of the aneurysm [6], Kirschner wires (K-wire) [7], orthodontic archwires [8], ligature wire [9], surgical sutures and versus staples [10]. Based on the application, such devices might be implanted either for a short or long time in the human body and regardless of the duration time, after finishing their mission, they should be removed from the body by a secondary operation.…”
Section: Introductionmentioning
confidence: 99%
“…Drawn wires from titanium (Ti) and its alloys, stainless steels (SSs), and nitinol have been used in different medical devices such as cardiovascular stents [4], coronary guide catheter [5], coil occlusion of the aneurysm [6], Kirschner wires (K-wire) [7], orthodontic archwires [8], ligature wire [9], surgical sutures and versus staples [10]. Based on the application, such devices might be implanted either for a short or long time in the human body and regardless of the duration time, after finishing their mission, they should be removed from the body by a secondary operation.…”
Section: Introductionmentioning
confidence: 99%
“…In xation with k-wires, after reduction of the fracture, fragments are xed by passing these straight wires through the bone fragments. The most important restriction of this technique is the forward/backward movement of the fractured fragments along the wire, causing malunion or nonunion (4). After reduction, these wires do not provide compression between the fracture fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of foreign bodies within the human body is a rare phenomenon. It has been reported that materials such as Kirshner or cerclage wire, which are frequently used in orthopedic surgeries, migrate to different regions from the areas where they are applied, such as the clavicle, patella or olecranon [1][2][3][4][5][6][7]. In some rare cases, bullets have been observed to migrate to different regions of the body following a gunshot injury [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%